Liminality revisited: Mapping the emotional adaptations of women in carceral space - Jewkes, Yvonne (Punishment & society, 2021)
This article draws on interview data with women in two prisons in the UK to understand the emotionally nuanced and sensorially attuned relationship between confined individuals and carceral space. The article presents an ‘emotional map’ comprising: (i) living or ‘being’ spaces; (ii) free places; and (iii) ‘therapeutic spaces’ in prisons.This tri-spatial thematic analysis enables us to use Victor Turner’s concepts of ‘liminality’ and ‘communitas’ to uncover the complex, contradictory and sometimes transient emotions that permeate spaces in prison. This in turn allows us to explore the particular challenges that accompany transitional periods of adjustment to prison life, the environmental constraints that women in prison live with and navigate, and the careful ‘spatial selection’ strategies they implement in order to seek or avoid particular emotional states.